On the Empirical Validity of "Gendered Reactions to Terrorist Attacks Can Cause Slumps not Bumps" (Holman et al., 2022) - Michael Jetter; Kieran Stockley (Institute for Replication (I4R), 2023)
Holman et al. (2022; HMZ) propose women (compared to men) political leaders experience significant drops in public approval ratings after a transnational terrorist attack. After documenting how survey-based evaluations of then-Prime Minister Theresa May suffered after the 2017 Manchester Arena attack, HMZ assemble a country-quarter level panel database to explore the generality of their hypothesis. They report evidence suggesting women (compared to men) leaders systematically experience decreased public approval rates after major transnational terrorist attacks (p-value of 0.020). We find that result disappears once any of the following adjustments is implemented: (i) excluding election quarter covariates (p = 0.104); (ii) correcting objective coding errors in the election quarter covariates (p = 0.058); (iii) excluding the May-Manchester observation (p = 0.098); or (iv) clustering standard errors at the country level (p = 0.558). Exploring all 2⁵ combinations of the five control groups HMZ incorporate in their specification, none of them clears the 5% threshold of statistical significance once the corrected election quarter variables are employed. We conclude that the empirical evidence does not provide sufficient support for HMZ's abstract claim that "conventional theory on rally events requires revision: women leaders cannot count on rallies following major terrorist attacks."
Keywords: 330